Entrepreneurship dalam Lingkungan Sekolah di SMA PGRI 4 Palembang - Neta Dian Lestari; Diana Widhi Rachmawati; Erma Yuliani; Nova Pratiwi; Ida Suryani; Chandra Kurniawan; Januardi Januardi; Boby Agus Yusmiono; Hendri Gunawan; Riswan Aradea (IKIP PGRI Bojonegoro, 2019)
ABSTRACTThe purpose of community service activity is to instill the spirit of